2023
DOI: 10.1093/infdis/jiad090
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Primary Series and Booster Doses of Inactivated Coronavirus Disease 2019 Vaccine Against Omicron BA.2 Variant Infection in China: A Retrospective Cohort Study

Abstract: Background China has been using inactivated COVID-19 vaccines as primary series and booster doses to protect the population from severe to fatal COVID-19. We evaluated primary and booster vaccine effectiveness (VE) against Omicron BA.2 infection outcomes. Methods This was a 13-province retrospective cohort study of quarantined close contacts of BA.2-infected individuals. Outcomes were BA.2 infection, COVID-19 pneumonia or wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The GMTs of IgGs, which remained above the lower limit of seroconversion throughout the study period, might be explained by the persistence of specific immune memory cells allowing for antibody production following exposure to the relevant antigens. Overall, our findings show the clinical efficacy of boosting with TURKOVAC in preventing SARS-CoV-2 infection and reducing COVID-19 severity and are complementary to those from previous studies of various inactivated vaccines which reported low rates of infection, pneumonia, hospitalization, and death associated with SARS-CoV-2 infection after the administration of a booster dose [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…The GMTs of IgGs, which remained above the lower limit of seroconversion throughout the study period, might be explained by the persistence of specific immune memory cells allowing for antibody production following exposure to the relevant antigens. Overall, our findings show the clinical efficacy of boosting with TURKOVAC in preventing SARS-CoV-2 infection and reducing COVID-19 severity and are complementary to those from previous studies of various inactivated vaccines which reported low rates of infection, pneumonia, hospitalization, and death associated with SARS-CoV-2 infection after the administration of a booster dose [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…According to the World Health Organization (WHO) data, by December 2022, 50 vaccines have been approved by at least one country worldwide ( Chakraborty et al, 2023 ), which include whole virus live attenuated or inactivated, protein-based, viral vector, and nucleic acid vaccines ( Ndwandwe and Wiysonge, 2021b ). As of 1 December 2022, over 13 billion COVID-19 vaccine doses have been administered ( Tang et al, 2023 ). In China, as of 31 December 2022, China has reported more than 3.4 billion cumulative doses of the COVID-19 vaccines ( Ma et al, 2023 , Sun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] For example, our estimate was much lower than that of an mRNA vaccine found in an RCT conducted during the Delta-predominant period (95.3%; 95% CI, 89.5%-98.3%), 28 but was closer to that of a recombinant protein vaccine (47.8%; 95% CI, 22.6%-64.7%) in another RCT 29 conducted during the Omicron-predominant period. Furthermore, previous general population studies 25,27,[30][31][32] reported that the effectiveness of a booster dose of an Model 1 (left) was adjusted for age, sex, health care practitioner, diabetes, hypertension, chronic kidney disease, stroke, cancer, interval between the first and second doses, and interval between the latest dose and last contact. Model 2 (right) was further adjusted for calendar time of last contact.…”
Section: Comparisons With Previous Studies and Interpretationsmentioning
confidence: 99%